Methods and Technology of Diagnosis of Personal Spiritual Values of University Students - Violetta Lappo (Vasyl Stefanyk Precarpathian National University, 2022)
The article reflects the results of the empirical study of the problem of the young person's spiritual values formation. The importance of the study of the person's spiritual and valuable sphere of the future educator has been emphasized. The author has developed the determining criteria of high, efficient, medium and low levels of the spiritual values formation. The researcher offers a range of methods aimed at establishing the levels of spiritual values formation in students studying pedagogical specialties at university. Significant attention has been paid to the studying of the understanding dynamics by the students of the definition context "spiritual values", the scope of students' knowledge concerning components of the individual's spiritual values, ranking factors which influence the formation of the individual's spiritual values. The author proves that the raised problem becomes more current in modern pedagogy of the higher school. As the systematized study results have confirmed the hypothesis that a significant part of surveyed students do not have enough formed system of spiritual values. The article partially uses the author's materials published in the "Bulletin of Lugansk National University named after Taras Shevchenko" (series: Pedagogical Sciences, 7 (312) (2017), 63-76).